“Ethics Ready”? Governing Research Through Informed Consent Procedures - Florence Caeymaex; Carole Wenger; Félicien de Heusch; Jean-Michel Lafleur (International Journal of Qualitative Methods, 2023)
Social Scientists using ethnographic methods are increasingly confronted with ethical clearance procedures imposed by universities, national authorities, professional organizations and funders. In this article, we focus on informed consent procedures in particular and discuss how they govern fieldwork interactions. To do so, we first show how ethical clearance procedures in Europe have been influenced by biomedical science, creating a risk of “governing the social science research in the name of ethics” (Haggerty, 2004) through “anticipatory regulatory regimes” (Murphy and Dingwall, 2007). We subsequently discuss the implementation of ethical procedures negotiated with an ethical review panel in the framework of an EU-funded project in migration studies. In doing so, we show how Research Ethics Committees (RECs) can incentivize researchers to comply with ethical guidelines and procedures in order to be considered as “ethics ready” by the funder. Providing examples of different ethnographic situations, we argue that —while informed consent procedures might reinforce participants’ vulnerabilities— they can also activate their desire to assert power. The article concludes with three recommendations that call for a redefinition of the relationships between institutions, researchers and participants through a co-construction of research ethics.